A Gauge Invariance of the Schrodinger Equation

Summary
Find in a quick way to prove gauge invariance without entailing a ton of messy math
Given the schrodinger equation of the form $$-i\hbar\frac{\partial \psi}{\partial t}=-\frac{1}{2m}(-i\hbar \nabla -\frac{q}{c}A)^2+q\phi$$
I can plug in the transformations $$A'=A-\nabla \lambda$$ , $$\phi'=\phi-\frac{\partial \lambda}{\partial t}$$, $$\psi'=e^{-\frac{iq\lambda}{\hbar c}}\psi$$
$$-i\hbar\frac{\partial \psi'}{\partial t}=(-\frac{1}{2m}(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)^2+q\phi-q\frac{\partial \lambda}{\partial t})\psi'$$.

Now when act on $$\psi'$$ on the right hand side, I come across the term $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)^2\psi'$$
I now that $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)\psi'=e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)\psi$$, but can I just say that $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)^2\psi'=e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)^2\psi$$, and if so, why? (In other words, is there a reason why I could simply do this twice rather than multiplying everything out, which gets messy). Thanks.
 
Why not? Your exponential factor is just a number, and it commutes with every operator inside the parentheses.
 

vanhees71

Science Advisor
Insights Author
Gold Member
13,460
5,352
The exponential is not just a number, because ##\lambda=\lambda(t,\vec{x})##. The problem with #1 is the gauge transformation of the em. field and several sign mistakes. The SGE reads (with ##\hbar=c=1##)
$$\mathrm{i} \partial_t \psi = -\frac{1}{2m} (-\mathrm{i} \vec{\nabla}-q \vec{A})^2 \psi + q \phi \psi.$$
Now you make
$$\psi'=\exp(\mathrm{i} q \lambda), \quad \vec{A}'=\vec{A}+\vec{\nabla} \lambda, \quad \phi=\phi-\partial_t \lambda.$$
Then ##\psi'## with the potentials ##\phi'## and ##\vec{A}'## fullfills the same SGE as ##\psi## with the potentials ##\phi## and ##\vec{A}##, i.e., the physics is invariant under gauge transformations, because ##\psi'## differs from ##\psi## only by a phase factor and the potentials only by a gauge transformation, which doesn't change the physical fields ##\vec{E}## and ##\vec{B}##.
 
I know it is gauge invariant. I suppose it is not clear the issue I am having. I know it is the case that
$$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)\psi'=e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)\psi$$.
I want to know if it is trivially true that $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)^2\psi'=e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)^2\psi$$. In other words could I simply just say that the operator $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)$$ acts on $$\psi'$$ twice., or do I need to show that $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)\psi=e^{-\frac{iq\lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)^2\psi$$?.
 
If you understand why the first equation in your post #4 holds, it should be obvious that also the last equation holds. I am not really sure what you want to shortcut here...
 

vanhees71

Science Advisor
Insights Author
Gold Member
13,460
5,352
You don't need to do anything more to "short cut". If the 1st. equation in #4 holds for all (sic) functions ##\psi##, then the 2nd equation follows immediately without any further calculation.
 
Perhaps it is a silly question. I was just wondering why it held. Thank you.
 
Well, did you go through the logic that leads to the first equation? Can you apply the same reasoning with ##\Phi = (-i\hbar\nabla - q/c A)\Psi## as a the function?
 
So $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)\psi'=(-i\hbar \nabla e^{-\frac{iq \lambda}{\hbar c}}\psi -\frac{q}{c}Ae^{-\frac{iq \lambda}{\hbar c}}\psi+\frac{q}{c}\nabla \lambda e^{-\frac{iq \lambda}{\hbar c}}\psi)=(-\frac{q}{c}\nabla\lambda e^{-\frac{iq \lambda}{\hbar c}} \psi-i\hbar \nabla\psi e^{-\frac{iq \lambda}{\hbar c}}-\frac{q}{c}Ae^{-\frac{iq \lambda}{\hbar c}}\psi+\frac{q}{c}\nabla \lambda e^{-\frac{iq \lambda}{\hbar c}}\psi)=e^{-\frac{iq \lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)\psi$$.

The issue I am having trouble understanding is why this would imply $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)^2\psi'=e^{-\frac{iq \lambda}{\hbar c}}(-i\hbar \nabla -\frac{q}{c}A)^2\psi$$. Wouldn't $$(-i\hbar \nabla -\frac{q}{c}A+\frac{q}{c}\nabla \lambda)$$ also act on $$(-i\hbar \nabla -\frac{q}{c}A)$$?
 
Wait. Just figured it out. Thank you.
 

Want to reply to this thread?

"Gauge Invariance of the Schrodinger Equation" You must log in or register to reply here.

Related Threads for: Gauge Invariance of the Schrodinger Equation

  • Last Post
Replies
3
Views
1K
Replies
2
Views
2K
  • Last Post
Replies
4
Views
4K
  • Last Post
Replies
6
Views
2K
Replies
7
Views
2K
  • Last Post
Replies
8
Views
926
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
7
Views
3K

Hot Threads

Top